(untitled) (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Haryono, Wahyudewantoro G. 2020. The alien freshwater fish of Mount Galunggung, West Java, Indonesia. Biodiversitas 21: 1401-1408. Mt. Galunggung, located in West Java, Indonesia, is an active volcano renowned for its deadly eruption in 1982. This area has many waters bodies, but the fish communities have not been recorded, especially the alien or introduced fish species. Hence, the objective of the present study was to determine the alien fish diversity, abundance, local distribution and utilization in Galunggung vicinity. The study was done in March 2013 using survey method covering 10 stations. Fish sampling was based on catch per unit of effort (CPUE) using mainly electrofishing, gillnet and cast net. A total of 24 species were recorded during the survey, in which 13 were listed as introduced species. Poecilia reticulata was the dominant species with 7.4 ind./St and followed by Xiphophorus helleri with 5.3 ind./St. Both species were also widely distributed on the sites with 70% local distribution. The alien species in this area are mostly used for ornamental fish.